2014
DOI: 10.13183/jcrg.v3i2.81
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Determinants of Health and Pregnancy Outcomes: A Retrospective Cohort Study in Tabriz

Abstract: Ab s t r a c tPurpose: To assess the effects of social determinants of health on pregnancy outcome in rural and urban areas of Tabriz.Methods: A retrospective cohort study design was used to examine 600 pregnant women who attended antenatal health care services in Tabriz, Iran from August 2012 to the October 2013. They were followed up from the sixth week of gestation to three months after delivery. Socioeconomic indicators and some other measures such as body mass index, family income status, maternal educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Generation of Results As shown in Figure 2, evaluating the relationship between education and preterm birth, Alizadeh et al showed that preterm birth is more common in illiterate compared to educated women. The odds of preterm birth were 4.31 times higher in illiterate compared to educated women (2.64%-7.03%: 95% CI) (36); but in the studies by Neshat et al (33), Mirzaei et al (30), and Sehati Shafaei et al (29), this was not statistically significant (P > 0.05). In 5 studies that examined the relationship between job and preterm birth, there was no statistically significant relationship between woman ' s job and preterm birth (29,30,36,37,39).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Generation of Results As shown in Figure 2, evaluating the relationship between education and preterm birth, Alizadeh et al showed that preterm birth is more common in illiterate compared to educated women. The odds of preterm birth were 4.31 times higher in illiterate compared to educated women (2.64%-7.03%: 95% CI) (36); but in the studies by Neshat et al (33), Mirzaei et al (30), and Sehati Shafaei et al (29), this was not statistically significant (P > 0.05). In 5 studies that examined the relationship between job and preterm birth, there was no statistically significant relationship between woman ' s job and preterm birth (29,30,36,37,39).…”
Section: Resultsmentioning
confidence: 83%
“…The odds of preterm birth were 4.31 times higher in illiterate compared to educated women (2.64%-7.03%: 95% CI) (36); but in the studies by Neshat et al (33), Mirzaei et al (30), and Sehati Shafaei et al (29), this was not statistically significant (P > 0.05). In 5 studies that examined the relationship between job and preterm birth, there was no statistically significant relationship between woman ' s job and preterm birth (29,30,36,37,39). Moreover, in the review of the relationship between the place of residence and preterm birth, the difference was not statistically significant between the prevalence of preterm birth in women living in rural areas compared to urban residents (29,39).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations